Branding in a multichannel retail environment: online stores vs. app stores and the effect of product type - Rezaei, Sajad; Valaei, Naser * (Emerald, 2017)
Purpose: The aim of this study is to investigate the structural relationship between online brand equity, brand experience, brand attitude, and brand attachment while considering the moderating effect of store type (online stores vs. app stores) and product type.